(untitled) - Samaha, Joel (Belmont, CA, 2003)
Thorough, mainstream introduction to the criminal justice system that explores both the formal (legal) and informal (behaviors, actions, judgements) dimensions of each part of the process. Covers the traditional core of the criminal justice system (police, courts, and corrections), focusing on the decision- making and evaluation of criminal justice policies and practices. Takes a provocative view of the CJ system to encourage critical thinking, providing a realistic look at problems as well as new programs which offer promise for the future. Dramatic scenarios and thought-provoking presentation of both sides of controversial criminal justice issues inject slices of Samaha's award-winning teaching style into the text
Keywords: Criminal justice, Administration of; United States